Computational Analysis of Thermal Building in a No-uniform Thermal Environment - Norfadzilah, Jusoh (Elsevier Ltd, 2015)
To predict of the thermal sensation of people located in no-uniform environment, it is very important to define the local heat transfer detail. In this context, the purpose was to make thermal comfort comparison between temperature settings of air conditioning. The temperature was maintained at five different levels which are 19 °C, 21 °C, 23 °C, 26 °C and 29 °C. A Computational Fluid Dynamic (CFD) model of an office was built. It was given similar geometries, boundary conditions and heat sources outputs as a real life test room that was used for measurement. In this study, CFD is applied to predict the thermal sensation of people with modified temperature setting. The comparison of thermal comfort parameters between the field measurement and modeling simulation was done and the result CFD was observed to predict the functionality of modified temperature setting. The analysis shows that the highest temperature setting which is 29 °C, indoor environment increase compared the lowest temperature setting. It is intended to contribute to the effort towards designing and instrumenting buildings that provide cleaner and more comfortable environment and for obtaining maximum energy savings.